Analisis Pengaruh Paparan Kebisingan, Suhu dan Kelembaban Udara terhadap Tekanan Darah Karyawan - Prandika, Dores; Haryandi, Haryandi (Department of Pharmacy, Bumigora University, 2022)
Health and safety at work at PT Santosa Utama Lestari needs to be improved in order to provide a sense of comfort for workers, both directly and indirectly, in some parts or the possibility of having dangerous risk factors due to exposure, temperature and humidity, this is caused by industries that are active with the use of production machines in the corn drying industrial activities of PT. Santosa Utama Lestari Bima Unit. This study aims to analyze the effect of exposure to blood, temperature and humidity on the pressure of employees at PT. Santosa Utama Lestari Bima Unit. This research uses descriptive qualitative data analysis method. Based on the results of this study, the results of the effect of the intensity of the intensity, temperature and humidity at work on systolic blood pressure can be seen the coefficient of determination of the R Square value of 0.166 which implies that the influence of the independent variables (noise, temperature and air) simultaneously on the variables (blood pressure) systolic) was 16.6% percent. While the remaining 80.4% is influenced by factors outside the variables of this study. While the diastolic pressure can be seen the coefficient of determination R Square value of 0.246 which implies that the effect of the independent variables, temperature and humidity simultaneously on the variable (Dystolic pressure) is 0.61%, while the remaining 93.9% is influenced by other factors. outside of this research.